Ideological Differences in Anchoring and Adjustment During Social Inferences. (November 2016) - Stern, Chadly; West, Tessa V.
Recent research has demonstrated that conservatives perceive greater similarity to political ingroup members than do liberals. In two studies, we draw from a framework of "anchoring and adjustment" to understand why liberals and conservatives differ in their perceptions of ingroup similarity. Results indicate that when participants made judgments under time pressure, liberals and conservatives did not differ in assuming ingroup similarity. However, when participants were given sufficient time to make judgments, liberals assumed less similarity than conservatives did, suggesting that liberals adjusted their judgments to a greater extent than conservatives did (Studies 1 and 2). In examining an underlying motivational process, we found that when conservatives' desire to affiliate with others was attenuated, they adjusted their initial judgments of ingroup similarity to a similar extent as liberals did (Study 2). We discuss implications for research on ideology and social judgment.